Analisis Pengaruh Harga dan Kualitas Layanan terhadap Keputusan Konsumen Menggunakan Jasa Transportasi Online Maxim di Makassar - Kapriani Kapriani; Asmawiyah Asmawiyah; Salmiyah Thaha; Hariyanti Hariyanti (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2021)
This study aims to determine the effect of price and service quality on consumer decisions to use Maxim online transportation services in Makassar. The data collection technique was done by interview and questionnaire. The data used in this study are primary and secondary data. This research uses incidental sampling method with a sample size of 84 respondents. The results showed that based on multiple linear regression analysis showed that the variable price (X1) and service quality (X2) had a positive influence on consumer decisions. From the results of the calculation of the correlation coefficient (R) test, the R value is 0.828, indicating a very strong correlation. The coefficient of determination (R2) is 0.686. This means that the consumer's decision to use Maxim online transportation services is influenced by the price and service quality of 68.6%. Based on the results of the t test, it shows that the variable price (X1) and service quality (X2) have a significant effect on consumer decisions to use Maxim online transportation services in Makassar. The F test shows that the variable price and service quality simultaneously have a significant effect on consumer decisions to use Maxim online transportation services in Makassar. Thus the hypothesis proposed in this study is accepted.